2016
DOI: 10.1007/s00280-016-3057-z
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 gene polymorphism is associated with toxicity and clinical efficacy of irinotecan-based chemotherapy in patients with advanced colorectal cancer

Abstract: UGT1A1 gene polymorphism predicts irinotecan-related adverse reactions in advanced CRC patients of Xinjiang Uygur and Han nationality; UGT1A1 gene polymorphism is correlated with efficacy and prognosis in Uygur nationality, but only related to prognosis in Han nationality in irinotecan-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
1
35
1
1
Order By: Relevance
“…Both UGT1A1*6 and UGT1A1*28 related to G3–4 neutropenia, rather than delayed diarrhea, which was consistent with several large-sample analysis in Asia [47]. Several small-sample analyses also noted that UGT1A1*28 and UGT1A1*6 could predict severe irinotecan-induced severe diarrhea [21, 22], which did not appear in the current study. A small sample analysis of Atasilp C et al, involving UGT1A1*6 and UGT1A1*28 were included in this analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Both UGT1A1*6 and UGT1A1*28 related to G3–4 neutropenia, rather than delayed diarrhea, which was consistent with several large-sample analysis in Asia [47]. Several small-sample analyses also noted that UGT1A1*28 and UGT1A1*6 could predict severe irinotecan-induced severe diarrhea [21, 22], which did not appear in the current study. A small sample analysis of Atasilp C et al, involving UGT1A1*6 and UGT1A1*28 were included in this analysis.…”
Section: Discussionsupporting
confidence: 91%
“…However, the UGT1A1*28 TA6/6 and TA7/7 genotypes may show an increased treatment response according to our results. In contrast to our results, Xu et al 67 observed different clinical responses in Ugyur patients with different UGT1A1*28 polymorphism genotypes, but not in the Han population. Although the reduction of irinotecan was greater in patients with the TA7/7 or TA6/7 genotypes than the TA6/6 genotype, no difference in overall or progression-free survival between the two group patients were found by Dias et al 68.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Hirasawa et al26 found that UGT1A1*6 / *28 mutations are associated with an increased risk of neutropenia and delayed diarrhea at a low dose of CPT-11. In China, Xu et al3 discovered that mutant UGT1A1*6/*28 genotypes significantly increase the incidence of delayed diarrhea, and the incidence of neutropenia is significantly increased when the UGT1A1*6 and UGT1A1*28 genotypes are considered together. Further, Chinese patients with UGT1A1*6/*28 mutations are more likely to suffer delayed diarrhea than Japanese patients.…”
Section: Discussionmentioning
confidence: 99%